CD4-T Lymphocyte in Cervical Cancer Patients on Pre-and Post-Chemotherapy - Endah Indriastuti; Endang Retnowati; Wita Saraswati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Introduction : Cervical cancer is a gynecology cancer with the highest incidence in the Dr.Soetomo Hospital, Surabaya. Neoadjuvant chemotherapy with cisplatin has been used to increase radiosensitivy of cancer cells before radiotherapy done in advanced stage cervical cancer patients. This research aimed to know the differences of CD4-T lymphocyte profile in stage IIIB patient before and after chemotheraphy administration.Methods : This research was done in February-September 2018. Seventeen patients out of 31 stage IIIB cervical cancer patients planned to receive neoadjuvan chemotherapy with cisplatin every 3 weeks for 3 series were checked for the CD4+ T lymphocyte count and percentage. The examinations were done before the first and after the third chemotherapy administration.Results : Mean±SD of the CD4-T lymphocyte count before chemotherapy was 817±314 cells/μL and mean±SD of the CD4-T lymphocyte  percentage was 38.96±8.47%. While mean±SD of the CD4-T lymphocyte count after chemotherapy was 881±335 cells/μL and mean±SD of the CD4-T lymphocyte percentage was 39.01±8.50%. There was no significant  difference of CD4-T lymphocyte count between before and after chemotherapy (p=0.471). There was also no significant difference of CD4-T lymphocyte percentage between before and after chemotherapy (p=0.866). Both the CD4-T lymphocyte count and percentage tended to increase in postchemotherapy condition.Conclusion : The CD4-T lymphocyte count and percentage were not significantly different between before and after chemotherapy administration in stage IIIB cervical cancer patients. Both the CD4-T lymphocyte count and percentage tended to increase in postchemotherapy condition.